Liderança visionária: um estudo com executivos no contexto organizacional brasileiro - Behmer, Sara Isabel (2005)
Leadership has been considered one of the basic issues for a successful company in the contemporary world since there is an upward demand for leaders that are able to sustain the Agency s success. The concept of Agency has to be understood as professionals that are in leadership positions inside the organization and are working for the stockholders. Among the many leadership theories developed in the last ten decades there is the group of Contemporary Leadership Theories and in this group there is one theoretical approach that outstands, the Visionary Leadership approach developed by Burt Nanus in 1992. This approach suggests a way of leadership that holistically benefits the organization which results are reflected in every stakeholder. Organizations inevitably achieve success under this kind of management. Therefore the purpose of this study is to analyze if nowadays successful leaders agree with the approach suggested by Burt Nanus and if they do so, how this is put into practice. In order to obtain the data for this study, a research was conducted with the first leader of many profit-oriented companies. Data were collected through a questionnaire using the Likert 5 possibilities scale in order to asses the degree of agreement / disagreement with the Visionary Leadership concepts. Also was researched with those leaders, which were the recognized drivers that lead to the development of this leadership style. The obtained results point that the researched leaders considers themselves visionary leaders, validating the visionary leadership concept and suggesting ways to be used in its development. From this data was possible to reflect about the importance of investing in people to add value to the company